2019
DOI: 10.1080/17518423.2019.1645224
|View full text |Cite
|
Sign up to set email alerts
|

A Parenting Program to Reduce Disruptive Behavior in Hispanic Children with Acquired Brain Injury: A Randomized Controlled Trial Conducted in Mexico

Abstract: Children with acquired brain injury (ABI) are at risk of impairments in self-regulation and disruptive behavior. We aimed to investigate the effectiveness of the Signposts program to reduce disruptive behavior and improve self-regulation in Hispanic children with ABI, and reduce parental stress and improve parenting practices. Using a randomized controlled trial design, we assigned children (n = 71) and their parents to Signposts or generic telephone support. Blinded assessors conducted assessments at pre-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Table 2 presents the characteristics of the included studies. Two RCTs were conducted in the USA [ 21 , 25 ], one RCT in Mexico [ 22 ], and one RCT in Australia [ 23 ]. Three RCTs were registered in a clinical trials database (Universal Trial Number U1111-1193689 [ 22 ], Clinicaltrials.gov NCT 01214694 [ 21 ], and Australian New Zealand Clinical Trials Registry ACTRN12610001051033 [ 23 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 presents the characteristics of the included studies. Two RCTs were conducted in the USA [ 21 , 25 ], one RCT in Mexico [ 22 ], and one RCT in Australia [ 23 ]. Three RCTs were registered in a clinical trials database (Universal Trial Number U1111-1193689 [ 22 ], Clinicaltrials.gov NCT 01214694 [ 21 ], and Australian New Zealand Clinical Trials Registry ACTRN12610001051033 [ 23 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs were conducted in the USA [ 21 , 25 ], one RCT in Mexico [ 22 ], and one RCT in Australia [ 23 ]. Three RCTs were registered in a clinical trials database (Universal Trial Number U1111-1193689 [ 22 ], Clinicaltrials.gov NCT 01214694 [ 21 ], and Australian New Zealand Clinical Trials Registry ACTRN12610001051033 [ 23 ]). The study recruitment periods were reported for three RCTs (2010 to 2015 [ 21 ], March 2016 to May 2017 [ 22 ], and October 2010 to May 2012 [ 23 ]), and were not reported in one RCT [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, poorer baseline behaviors may lead to more room for improvement in scores from pre-to postintervention, a result that was reflected in studies with children who had lower baseline behavior scores. 38,39 Taken together, child factors of age, baseline behavior, and time since injury are important considerations when examining the beneficial effects of parent interventions on child behavior, regardless of whether the behavior is internalizing or externalizing.…”
Section: Wwwheadtraumarehabcommentioning
confidence: 99%
“…Across all three reviews, the authors highlighted the general paucity of research on intervention studies for this population, despite great need. Studies tend to focus on families affected by pediatric traumatic brain injury in particular, though outcomes are mixed [ 91 , 92 , 93 , 94 , 95 ]. Of note, TIC is distinguished from these types of trauma-specific interventions designed to directly ameliorate the effects of past trauma [ 96 ].…”
Section: Resultsmentioning
confidence: 99%